2021
DOI: 10.3389/fpubh.2021.750551
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Campylobacter Species in Livestock, Humans, and Water in Livestock Owning Households of Peri-urban Addis Ababa, Ethiopia: A One Health Approach

Abstract: Campylobacter is the most common cause of bacterial infectious diarrhea and acute gastroenteritis globally, and is recognized as a significant zoonotic pathogen. Antimicrobial resistance amongst Campylobacter isolates is a significant global concern. A cross-sectional study was conducted to identify and characterize Campylobacter species in humans, animals and water sources in livestock owning households of peri-urban Addis Ababa, Ethiopia; and to characterize antimicrobial resistance. A total of 519 fecal sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 67 publications
7
15
1
Order By: Relevance
“…(27 MDR phenotypes). In accordance with our findings was the 95.5% resistance to three or more classes of antimicrobials noted by Chala et al [64] of bacterial isolates recovered from humans, animals and water sources in livestock-owning households, residing in the peri-urban areas of Addis Ababa, Ethiopia. It is striking and a call for concern that almost all the isolates belonging to Enterobacteriaceae (Yersinia spp., Salmonella spp.…”
Section: Discussionsupporting
confidence: 93%
“…(27 MDR phenotypes). In accordance with our findings was the 95.5% resistance to three or more classes of antimicrobials noted by Chala et al [64] of bacterial isolates recovered from humans, animals and water sources in livestock-owning households, residing in the peri-urban areas of Addis Ababa, Ethiopia. It is striking and a call for concern that almost all the isolates belonging to Enterobacteriaceae (Yersinia spp., Salmonella spp.…”
Section: Discussionsupporting
confidence: 93%
“…The MDR rate reported in this study is much higher than what has been reported in some European nations; for instance, in Poland, where MDR for Campylobacter isolates from raw chicken meat was 7% [ 40 ]. However, the findings of this study are concordant with some studies in other African countries: 95% of the Campylobacter isolates from broiler in Morocco displayed drug resistance to ≥3 drugs [ 33 ]; 95.5% of isolates from livestock (cattle and shoat), poultry, human, and water in Ethiopia [ 39 ]; 94.7% of the strains from poultry in Ghana [ 47 ], and 32.5% of in Campylobacter isolates from beef cattle in South Africa [ 42 ]. The observed discrepancies in MDR in Campylobacter may possibly be explained by the following: (1) level of intensification and type of production system; (2) the introduction and implementation of legislation to minimize antimicrobial use in livestock in European countries.…”
Section: Discussionsupporting
confidence: 88%
“…Notably, significant 63.1% ciprofloxacin-resistant isolates (69% C. coli and 60.8% C. jejuni) compared to strains resistant to nalidixic acid at 35.9% (10.3% C. coli and 45.9% C. jejuni ) were reported in this study. The observed resistance to ciprofloxacin is comparable to other studies in Kenya [ 12 ], Ethiopia [ 39 ], and Poland [ 40 ]. The relatively low resistance to nalidixic acid observed in this study is in contrast with those on Campylobacter isolates from backyard chicken in Central Kenya, where resistance to nalidixic acid was observed at 77.4% [ 12 ].…”
Section: Discussionsupporting
confidence: 86%
“…Frontiers in Microbiology 07 frontiersin.org of farms in peri-urban Addis Ababa, Ethiopia (Chala et al, 2021). Higher Campylobacter frequencies are generally expected in poultry, so the differences in frequencies might be because the latter study was conducted on farms that kept only livestock.…”
Section: Adjusted Ratio Pr (95% Ci)mentioning
confidence: 99%